Pengaruh Teknik Relaksasi Otot Progresif Terhadap Tingkat Stres Kerja Pada Staf Puskesmas Banyuputih Situbondo - Finanin Nur Indana; Risda Ayu Tsabitah (PSYCOMEDIA : Jurnal Psikologi, 2021)
Job Stress Caused By Work Pressure, Lack Of Managerial Support, And The Risk Of Violence And Bullying. Stress Due To Work Experienced By Workers If Not Immediately Addressed Will Have An Impact Both For Themselves And The Company. This Study Aims To Assess The Effect Of Progressive Muscle Relaxation In Reducing Work Stress On public healts center Banyuputih Staff. The Study Design Was Quasi Experimental Pre-Post Test Without Control Group With 35 Samples By Purposive Sampling. The Results Of The Study Using The Wilcoxon Signed Ranks Test Statistical Test Obtained P-Value Of 0,000 (P < 0.05). This Means That There Was The Effect Of Progressive Muscle Relaxation To Reduce Work Stress. Research Recommendations That Progressive Muscle Relaxation Be Applied By Workers During The Work Process Be Evidence Based Practice For Occupational Health Nurses In Overcoming Work Stress On Workers.